2003
DOI: 10.1111/j.1600-0773.2003.pto930605.x
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Induction of Differentiation by Ginsenoside Rh2 in SMMC‐7721 Hepatocarcinoma Cell Line

Abstract: The aim of this study was to investigate the effects of ginsenoside Rh 2 (G-Rh 2 ) on differentiation of SMMC-7721 hepatocarcinoma cell line in culture. We studied G-Rh 2 -induced differentiation of SMMC-7721 cells through cell proliferation, cell morphology, ultrastructure, cell cycle, cell function and metabolism. The proliferation of treated cells was inhibited, the morphology and ultrastructure seemed normal, the secretory amount and expression of a-foetoprotein, and the specific activity of g-glutamyl tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 24 publications
0
17
0
1
Order By: Relevance
“…The ability of Rh2 to suppress cell growth has also been observed in glioma cells [22,23] . Because Rh2 promotes neoplastic cells to return to a normal cell phenotype, it is expected to be a new type of anticancer agent [23] . It displays low toxicity, is associated with only a few side effects and is generally regarded as an anticancer nutrient [23] .…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The ability of Rh2 to suppress cell growth has also been observed in glioma cells [22,23] . Because Rh2 promotes neoplastic cells to return to a normal cell phenotype, it is expected to be a new type of anticancer agent [23] . It displays low toxicity, is associated with only a few side effects and is generally regarded as an anticancer nutrient [23] .…”
Section: Introductionmentioning
confidence: 92%
“…Because Rh2 promotes neoplastic cells to return to a normal cell phenotype, it is expected to be a new type of anticancer agent [23] . It displays low toxicity, is associated with only a few side effects and is generally regarded as an anticancer nutrient [23] . Although extensive investigations have shown that Rh2 exerts its antiproliferative effects through induction of an apoptotic pathway [24] , the role of miRNAs in this process has not yet been explored.…”
Section: Introductionmentioning
confidence: 99%
“…To understand the mechanism of action of Rh2, it is worth noting that the latent period before Rh2 manifests its effects on cultured cells is very different for its various effects. For example, it takes more than two days for Rh2 to induce the expression of differentiation markers (7,(16)(17)(18); however, it takes only 3 to 12 h for it to affect the activity of transcription factors (11,19,20). Rh2 affects cdks and cyclins (21), mRNA expression (18), and the phosphorylation level or activity of kinases (11,(22)(23)(24) in less than 60 min.…”
Section: Introductionmentioning
confidence: 99%
“…Low AFP levels indicate that differentiation of hepatoma cells was induced. 17,18) Therefore CT and CiLi may also induce hepatoma cell differentiation.…”
Section: Discussionmentioning
confidence: 99%